Kualitas Website Kendari Kota dalam Penanganan Covid-19 di Kota Kendari - Made Agus Abdiyanto; Muhammad I Nabiel A. (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2023)
The Kendarikota Website is a website managed by the Kendari City Communication and Information Office which aims to assist the performance of the Kendari City Communication and Information Office in terms of public services in the information sector, especially regarding the handling of Covid-19 (Kendari city website 2019 ). The study aims to determine the quality of the Kendarikota website as tool of information used in handling Covid-19 at the Kendari City Communication and Information Office and the strategy carried out by the Kendarikota Communication and Information Office to improve the quality of the Kendarikota website in handling Covid-19. The method used in this research is descriptive qualitative research method. The technique of collecting data and information is done by interview observation, documentation. Meanwhile, the technique of data analysis is done by data reduction, data presentation, and drawing conclusions. Research shows that the quality of information, service quality, and technical quality presented on the Kendarikota website can be said to have good information accuracy and website performance. Therefore, strategies in Improving Technical Quality, Service Quality and Engineering Quality are also good. It can be concluded from the quality of the Kendarikota website in Handling Covid-19 in Kendari City if measured by Alvaro Rocha's theory about website quality has been implemented well, then the Strategy for Improving Content Quality, Service Quality and Technical Quality is quite good in its implementation.